2013
DOI: 10.1186/1471-2164-14-34
|View full text |Cite
|
Sign up to set email alerts
|

Developmentally regulated expression and complex processing of barley pri-microRNAs

Abstract: BackgroundMicroRNAs (miRNAs) regulate gene expression via mRNA cleavage or translation inhibition. In spite of barley being a cereal of great economic importance, very little data is available concerning its miRNA biogenesis. There are 69 barley miRNA and 67 pre-miRNA sequences available in the miRBase (release 19). However, no barley pri-miRNA and MIR gene structures have been shown experimentally. In the present paper, we examine the biogenesis of selected barley miRNAs and the developmental regulation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 48 publications
(83 citation statements)
references
References 82 publications
6
77
0
Order By: Relevance
“…Pri-miRNAs contain introns, and widespread alternative splicing of pri-miRNA transcripts has been detected (Mica et al, 2009;Szarzynska et al, 2009;Kruszka et al, 2013). In Arabidopsis, alternative splicing of pri-miR162a (Hirsch et al, 2006) or the pri-miR842-miR846 dicistron (Jia and Rock, 2013) disrupts miRNA-containing stem-loops and reduces the accumulation of processed miRNAs.…”
Section: Splicingmentioning
confidence: 99%
“…Pri-miRNAs contain introns, and widespread alternative splicing of pri-miRNA transcripts has been detected (Mica et al, 2009;Szarzynska et al, 2009;Kruszka et al, 2013). In Arabidopsis, alternative splicing of pri-miR162a (Hirsch et al, 2006) or the pri-miR842-miR846 dicistron (Jia and Rock, 2013) disrupts miRNA-containing stem-loops and reduces the accumulation of processed miRNAs.…”
Section: Splicingmentioning
confidence: 99%
“…The 39 end of pri-mRNA is modified by the cleavage and polyadenylation machinery that adds a poly(A) tail to the 39 end of all pri-mRNAs. Moreover, many plant pri-miRNAs, like most mRNA precursors (pre-mRNA), contain introns that are excised by the spliceosome (Szarzynska et al, 2009;Kruszka et al, 2013;Zielezinski et al, 2015). We have recently shown that the splicing of such introns from pri-miRNAs, or more precisely their active 59 splice sites, stimulates miRNA maturation (Bielewicz et al, 2013;Schwab et al, 2013).…”
mentioning
confidence: 99%
“…For the small RNA library construction and stem-loop reverse transcription, total RNA enriched for small RNAs was isolated from 100 mg of 14-day-old A . thaliana seedlings using a previously described protocol [46]. The integrity and quality of the NGS-dedicated RNA were verified using an Agilent RNA 6000 Nano Kit (Agilent Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…The RNA electrophoresis, blot transfer and hybridization were performed as previously described [46,50]. All hybridizations were performed with three biological replicates.…”
Section: Methodsmentioning
confidence: 99%